Bitter tastes turn sweet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A new sorghum variety with low levels of tannin has been developed by researchers of the Serere Agricultural and Animal Production Research Institute in Uganda. Tannin gives a bitter taste to common sorghums but this variety tastes almost sweet. It...